TRAINING IN MEDIATION: APPLICATION ON THE COMMUNICATION MODEL - Portere, Viktorija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Teaching the participants of the conflict to conduct a communication is an important process in the mediation. A positive result of the mediation, i.e., resolution of the conflict, is impossible without teaching the participants the rules of a conflict-free communication; that will allow them to avoid conflict situations in society also in future. The publication considers a model of communication between the participants in the conflict as well as the mediator. The model is built on the basis of an analysis of the principles of existing communication models and experience of a practicing mediator. The types of communication noises (including constructs as communication barriers) have been identified and classified, and techniques for detecting these noises has been proposed. By selecting and studying them the mediator has the opportunity to effectively arrange a training for the participants of the conflict. The objective of the study is to build a communication model in a mediation, taking into account semantic and psychological noises; to demonstrate the role of a mediator in a constructive conflict resolution for dialogue teaching; to determine the mediator’s tools. The theoretical study is based on the analysis and assessment of philosophical, pedagogical and psychological literature and a mediation practice. Results: a model of communication in the process of mediation, questionnaire for identifying noises and a processing algorithm for it to determine the methodology for teaching communication to the participants of the conflict.